A Randomized, Phase II Trial of Standard Triweekly Compared with Dose-Dense Biweekly Capecitabine Plus Oxaliplatin Plus Bevacizumab as First-Line Treatment for Metastatic Colorectal Cancer: XELOX-A-DVS (Dense Versus Standard) - Hurwitz, Herbert (AlphaMed Press, 2012)
BACKGROUND. Capecitabine administered for 7 days biweekly with oxaliplatin (XELOX) biweekly has been reported to have activity and safety profiles similar to those of standard capecitabine given for 14 days triweekly. Multiple studies have shown that the addition of bevacizumab to 5-fluorouracil–based chemotherapy is active and well tolerated. METHODS. Patients with metastatic colorectal cancer (mCRC) were randomized to XELOX plus bevacizumab using a standard triweekly cycle (Q3W) or a dose-dense biweekly cycle (Q2W) schedule. The primary endpoint was the progression-free survival (PFS) interval. This trial is registered on ClinicalTrials.gov (identifier, NCT00159432). RESULTS. In total, 435 U.S. patients were randomized. The median PFS intervals were 9.6 months in the Q3W group and 9.1 months in the Q2W group. The median overall survival times were 28.4 months and 22.1 months and the median times to treatment failure were 5.5 months and 3.4 months, respectively. Overall, gastrointestinal disorders were the most common (93%) adverse event (AE). Grade 3 or 4 AEs occurred in 75% and 81% of patients in the Q3W and Q2W groups, respectively. Treatment discontinuation as a result of diarrhea (5% versus 10%) and hand–foot syndrome (2% versus 9%) was less common in the Q3W group than in the Q2W group, respectively. CONCLUSIONS. Based on these results, the first-line treatment of U.S. patients with mCRC using a biweekly combination of XELOX and bevacizumab at the doses studied cannot be recommended. XELOX Q3W remains the preferred schedule for the management of mCRC.